Potential Productivity of Edible Podded Pea Cultivars in Mid-Hills of Himachal Pradesh, India - A. K. Thakur; H. S. Kanwar; Manish Kumar; Amit Vikram; Rakesh Kumar (International Journal of Economic Plants)
Five cultivars of edible podded peas with 4 replications were evaluated during rabi 2013-14 at Department of Seed Science and Technology, Dr Y S Parmar University of Horticulture and Forestry, Solan, HP, India for their potential productivity. The observations were recorded on pod weight, pod plant-1, pod size, pod and seed yield, pod surface colour, stringiness, development of parchment layer and sweetness.  Mithi Phali recorded the maximum pod yield of 13.17 t ha-1 followed by variety Toledo Sugar yielded 12.60 t ha-1. The days to 50% flowering was observed earliest in Mithi Phali i.e. 111.33 days after sowing whereas the Arka Sampoorna took longest time (114 Days) to flower. The pods of Mithi Phali and Toledo Sugar were categorized as very sweet while all other varieties were comparatively less sweet. The maximum seed yield of 14.0 q ha-1 has been recorded in Mithi Phali closely followed by Toledo Sugar (13.31 q ha-1). The overall results obtained from this experimentation revealed that the variety Mithi Phali performed well with respect to majority of the parameters recorded under this study.